2018
DOI: 10.3390/ijms19051421
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability Occurs Rarely in Patients with Cholangiocarcinoma: A Retrospective Study from a German Tertiary Care Hospital

Abstract: Immune-modulating therapy is a promising therapy for patients with cholangiocarcinoma (CCA). Microsatellite instability (MSI) might be a favorable predictor for treatment response, but comprehensive data on the prevalence of MSI in CCA are missing. The aim of the current study was to determine the prevalence of MSI in a German tertiary care hospital. Formalin-fixed paraffin-embedded tissue samples, obtained in the study period from 2007 to 2015 from patients with CCA undergoing surgical resection with curative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 23 publications
1
39
0
1
Order By: Relevance
“…While cancers with deficient mismatch repair (dMMR) or microsatellite instability-high (MSI-H) are likely to benefit from anti-PD-1 inhibitor (eg, pembrolizumab [Keytruda]), BTCs are infrequently MSI-H or dMMR. 9 In the KEYNOTE-028 phase Ib basket trials across 20 advanced solid tumor types that include advanced BTCs, patients with high tumor mutation burden (TMB) and/or PD-L1 expression demonstrated higher response rates and better progression-free survival (PFS). 10 Follow-up studies on patients with advanced BTCs treated with immunotherapy in the KEYNOTE-158 (phase II) and KEYNOTE-028 (phase Ib) trials present preliminary evidence showing durable clinical outcome regardless of PD-L1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…While cancers with deficient mismatch repair (dMMR) or microsatellite instability-high (MSI-H) are likely to benefit from anti-PD-1 inhibitor (eg, pembrolizumab [Keytruda]), BTCs are infrequently MSI-H or dMMR. 9 In the KEYNOTE-028 phase Ib basket trials across 20 advanced solid tumor types that include advanced BTCs, patients with high tumor mutation burden (TMB) and/or PD-L1 expression demonstrated higher response rates and better progression-free survival (PFS). 10 Follow-up studies on patients with advanced BTCs treated with immunotherapy in the KEYNOTE-158 (phase II) and KEYNOTE-028 (phase Ib) trials present preliminary evidence showing durable clinical outcome regardless of PD-L1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…In another recent German study performed in surgical specimens of CCA derived from resection, including 102 patients (35 iCCA, 42 pCCA, 25 dCCA), the prevalence of MSI was examined not only by IHC for the expression of MLH1, PMS2, MSH2, and MSH6, but also by pentaplex PCR for five quasimonomorphic mononucleotide repeats (BAT-25, BAT-26, NR-21, NR-22, and NR-24). Whereas in the IHC-based analysis, no loss of expression of DNA repair enzymes was observed, by PCR the authors found only 1% of MSI-high and 1% of MSI-low (99). Thus, in addition to highlight discrepancy between different techniques aimed at investigating MSI, this study argues against the actual relevance of MSI in CCA.…”
Section: Immunotherapymentioning
confidence: 56%
“…Microsatellite status was analyzed based on five commonly used markers of microsatellite sequence: BAT-25, BAT-26, NR-21, NR-22, and NR-24 using a fluorescencebased pentaplex polymerase chain reaction technique and capillary electrophoresis. 26,27…”
Section: Microsatellite Analysismentioning
confidence: 99%